Pelatihan Pembuatan Pengharum Ruangan Alami Aromakara sebagai Inovasi Produk Berbasis Bahan Rempah bagi Siswa MTsN 1 Kota Palangka Raya - Muhammad Nor; Jumrodah Jumrodah (Jurnal Pelayanan Masyarakat, 2025)
This community service activity aims to introduce and train students in the process of making AromaKara, a natural air freshener made from kitchen spices as a substitute for artificial fragrances containing volatile organic compounds (VOCs). The method applied in this community service activity is the Participatory Action Research (PAR) method, namely training and direct instruction which was carried out on Thursday, November 20, 2025, at 07.00 WIB at MTsN 1 Palangka Raya City, with a focus on 32 students in grades 8-1. The results of this activity showed an increase in students' understanding of the risks of using synthetic fragrances, the benefits of using natural ingredients, and environmental awareness. Students were also able to make Aromakara products independently and showed high interest during the activity. This training played a role in strengthening students' environmental literacy, scientific literacy, and entrepreneurial interests. Overall, this community service activity demonstrated the effectiveness of experiential learning in the MBKM program and the potential for sustainable development within the school environment.